Perpustakaan dalam Penumbuhan Sikap Gemar Membaca Siswa Madrasah - Rasyid, Saefuddin A. (Buletin Al-Turas, 2005)
In general, students reading interest is relatively low. Such lower interest implies at least to things in students learning process, especially in madrasahs-- a low appreciation toward the existence of a librarianship and teaching-learning process which is less innovative. Therefore it is necessary to develop strategic and technical steps- and programs- to create a conducive learning environment in which students reading interest increases.